Design and Implementation of 3D approach for Courseware Electromagnetic Theory Subject - Bakar, Norasiken; Shahbodin, Faaizah; Hasan, Hazmilah; Salam, Sazilah; Mad Lani, Shahdan (2011)
This paper will explain about research on development of three dimensional (3D) courseware for Electromagnetic Theory Subject (EMT) subject that have been offers to all Malaysia Technical University Network (MTUN). The EMT courseware was included a multimedia software, three dimensional environment, and exercises for student to be done to test their understanding after using the courseware. Moreover, this paper explain about the research methodology that include the development of the courseware for teaching and learning, the effectiveness of the 3D courseware for teaching and learning, and the use of ICT in education for universities level. In this research it is use of Constructivism-Cognitive-Contextual Model Life Cycle (C3MLC) model to construct the research, which it includes of Analysis phase, Design phase, Development phase, Implementation phase, Evaluation phase. After the first three phases have been completely done, courseware will be test to Subject Matter Expert (SME) to judge the reliability of the courseware for the learning usage. It includes past students and lecturers before the Evaluation phase be done to collect research sample, instrument, and methodology of collecting and analyzing data gathered.